JavaScript-Based Digital Universal Astrolabe and Its Accuracy Test in Qibla Direction Calculation - Nahwandi, M Syaoqi; Setyawan, Edy; Nadirin, Akhmad (University of Muhammadiyah Sumatera Utara, 2025)
The Astrolabe as a classical astronomical instrument, holds significant historical and educational value, yet its use has become limited due to technological advancements. This study aims to develop a JavaScript-based Universal Astrolabe software to digitize the functions of a physical Astrolabe, with a focus on testing the accuracy of Qibla direction calculations. The Research and Development (RD) method was implemented through stages of needs analysis, design, implementation, and accuracy testing. Test results from three locations (Cirebon, Kuala Lumpur, Istanbul) showed minor discrepancies (0°1'56